Controlled synthesis of N-doped carbon and TiO2 double-shelled nanospheres with encapsulated multi-layered MoO3 nanosheets as an anode for reversible lithium storage. Issue 31 (28th July 2020) - Wu, Jing; Zhang, Peilin; Liu, Jinzhe; Zhou, Chencheng; Guo, Shouzhi; Li, Shuo; Lei, Yuchen; Li, Kuang; Chen, Luyang
Abstract : Under the synergy of α-MoO3, TiO2, and NC, MoO3 @TiO2 @NC having a special hierarchical structure exhibits excellent electrochemical performance. Abstract : α-Phase molybdenum trioxide (α-MoO3 ) is one of the promising anode materials for lithium storage due to its high theoretical capacity and unique intercalation reaction mechanism. Herein, through an efficient step-by-step solvothermal synthesis strategy, multi-layered MoO3 nanosheets are encapsulated by nitrogen-doped carbon (NC) and ultrathin TiO2 double-shells to obtain hierarchical core–shell nanospheres (MoO3 @TiO2 @NC). The unique nanostructure enables shortening the Li + diffusion distance, buffer the volume change during the intercalation/deintercalation process, and increase the active sites for the electrochemical reaction. Based on the hierarchical nanostructure and the synergistic effect of each component, the MoO3 @TiO2 @NC electrode exhibits a high Li + storage capacity around 979.6 mA h g −1 after 200 cycles at 0.2 A g −1, a stable cycle performance of 800.3 mA h g −1 at 1 A g −1 after 700 cycles and an excellent rate capability of 418.0 mA h g −1 at 5 A g −1 . Furthermore, the MoO3 @TiO2 @NC-based coin-type full cell with a commercial LiNi1/3 Mn1/3 Co1/3 O2 cathode exhibited a good cycling stability at 0.2 A g −1 for 100 cycles (∼190 mA h g −1 ) and rate capability (134 mA h g −1 at 5 A g −1 ).